The en(Counter) of a deeper darkness: Ian McEwan’s Saturday - Hejaz, Neha; Singh, Rajni (Penerbit Universiti Kebangsaan Malaysia, 2020)
Drawing on the horror and dark side of knowledge, which is in discrete complicity with the rational and powerful bases of power–the present article focuses on Ian McEwan’s novel Saturday (2005). The paper attempts to draw analogies between the two set of characters Apollonian and Dionysian embodied in Henry Perowne and Baxter respectively. Perowne represents Western privilege and Baxter stands for the evil outsider. The absolute stable order of Perowne’s existence is challenged when he is involved in a car crash with a young man named Baxter who experiences violent mood swings as a symptom of Huntington’s disease. Saturday too, like most Ian McEwan’s novels engenders a tension between the two poles of human thought: doubt and faith, rational and intuitive, out of which this paper attempts to explore another facet of this dichotomy in the Nietzschean terminology of Apollonian and Dionysian spirit. By setting the novel in a single day in London, after 9/11 and during preparations for war in Iraq, McEwan affirms a constructivist theory of knowledge in literature where individuals and collectives (including novelists) participate in making up meaningful presents and liveable futures(a combination of two extremes of Apollonian and Dionysian).